Peningkatan Kapasitas SDM Kelompok Sadar Wisata Paingan Padang Pariaman melalui Pelatihan Pembuatan Paket Wisata - Rini Eka Sari; Novi Yanita; Yudhytia Wimeina; Zengga (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The community service activity aims to provide training and assistance to members of the Paingan Tourism Awareness Group (Pokdarwis) in making tour packages in the tourist village of Nagari Guguak Kuranji Hilir, Padang Pariaman Regency. This activity was carried out using the method of lectures, discussions and practice of making tour packages by Pokdarwis members totaling 10 people, located at the office of the Wali Nagari Guguak Kuranji Hilir, Padang Pariaman Regency. The result of this activity is the increase in knowledge and skills of Pokdarwis Paingan members in terms of designing and making tour packages based on the potential in their area and the production of a tour package entitled